2006
DOI: 10.1007/s11099-005-0159-y
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic responses of Populus przewalski subjected to drought stress

Abstract: Cuttings of P. przewalski were exposed to two different watering regimes which were watered to 100 and 25 % of field capacity (WW and WS, respectively). Drought stress not only significantly decreased net photosynthetic rate (P N ), transpiration rate (E), stomatal conductance (g s ), efficiency of photosystem 2 (PS2) (F v /F m and yield), and increased intrinsic water use efficiency (WUE i ) under controlled optimal conditions, but also altered the diurnal changes of gas exchange, chlorophyll fluorescence, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
77
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 46 publications
10
77
0
Order By: Relevance
“…P N , g s , C i , ambient CO 2 concentration (C a ), and PAR were measured at 07:00, 09:00, 11:00, 13:00, 15:00, 17:00, and 19:00 on a fully sunny day (September 3, 2006) under natural conditions to determine diurnal variation of gas exchange. Intrinsic water use efficiency (WUEi) was calculated by dividing P N by g s , and stomatal limitation value (L s ) was calculated using the following formula: L s = 1 -C i /C a according to Yin et al (2006). P N -PAR response curves were measured at 1 800, 1 500, 1 200, 1000, 800, 500, 200, 100, 50, 20, and 0 μmol(photon) m -2 s -1 of PAR under uniform conditions (25 °C, 330-350 μmol(CO 2 ) mol -1 , and 71-75 % RH) at 10:00-11:30 on two sunny days (September 5 and 7, 2006).…”
Section: Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…P N , g s , C i , ambient CO 2 concentration (C a ), and PAR were measured at 07:00, 09:00, 11:00, 13:00, 15:00, 17:00, and 19:00 on a fully sunny day (September 3, 2006) under natural conditions to determine diurnal variation of gas exchange. Intrinsic water use efficiency (WUEi) was calculated by dividing P N by g s , and stomatal limitation value (L s ) was calculated using the following formula: L s = 1 -C i /C a according to Yin et al (2006). P N -PAR response curves were measured at 1 800, 1 500, 1 200, 1000, 800, 500, 200, 100, 50, 20, and 0 μmol(photon) m -2 s -1 of PAR under uniform conditions (25 °C, 330-350 μmol(CO 2 ) mol -1 , and 71-75 % RH) at 10:00-11:30 on two sunny days (September 5 and 7, 2006).…”
Section: Plantsmentioning
confidence: 99%
“…Mass of the pot plus seedling at field capacity was adjusted accordingly. Chl fluorescence was determined on fully expanded exposed leaves (one leaf each plant) using a modulated fluorometer (PAM 2100, Walz, Effeltrich, Germany) on September 2, 2006 according to Roháček and Barták (1999) and Yin et al (2006). Initial fluorescence (F 0 ) and maximal fluorescence (F m ) were measured after a 30-min dark adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…The stomatal limitation value (Ls) was calculated using the formula Ls = 1 -Ci/Ca (where Ca is atmospheric CO2 concentration), in accordance with Yin et al (2006). Linear regressions of irradiance and PN over the range of 0-200 µmol photons of photosynthetically active radiation (PAR) m −2 s −1 were applied to determine the apparent quantum yield (AQY) of carbon assimilation (Yin et al 2006).…”
mentioning
confidence: 99%
“…Drought reduced above and below ground biomass (Table 3), and finally resulted in small plant, our results agreed with Casper's results (1996). Drought reduced plant productivity, because of plant increasing dissimilation and decreasing assimilation through affecting gas exchange, the diurnal pattern of gas exchange, photosynthesis PAR (photosynthetically active radiation) response curve, net photosynthetic rate, stomatal conductance, the maximal efficiency of PSII photochemistry, the actual quantum yield and the photochemical quenching (Williams and Black, 2004;Folkard et al, 2005;Yin et al, 2006). However, Llorens et al (2004) also found that draughted plants (Erica multiflora and Calluna vulgaris) were able to maintain higher leaf photosynthetic rates than control plants in relation to the accumulated rainfall over the months previous to the measurements.…”
Section: Discussionmentioning
confidence: 99%